Dynamic Linkages Between the Oil Spot, Oil Futures, and Stock Markets: Evidence from Dubai - Lamouchi, Rim Ammar; Alawi, Suha Mahmoud (International Journal of Energy Economics and Policy, 2019)
In this paper, we investigate the dynamic linkages between prices on the oil spot, oil futures, and energy stock markets in Dubai between June 29, 2010 and November 2, 2018. We apply a class of multivariate GARCH model to analyze this relationship. We also consider the corresponding markets in the United States, and in order to examine the volatility transmission among the three markets, we use the HAR model. Our empirical results reveal that the correlations between the three markets in Dubai are lower than in the US. We observe high levels of correlations before crises, but this was not the case during the crises themselves. Furthermore, we demonstrate the existence of volatility transmission between the oil spot and futures markets and the oil spot and energy stocks markets, while there is only a unidirectional effect from the energy stock market to the oil futures market. Overall, our findings are crucial for understanding the dynamics that exist between the three markets. Keywords: Oil prices, Stock market, DCC-GARCH, VAR. JEL Classifications: G12, Q43 DOI: https://doi.org/10.32479/ijeep.8705